Pengaruh Dukungan Sosial dan Tuntutan Pekerjaan dalam Niat Meninggalkan Pekerjaan (Studi pada Karyawan Sewing PT Dan Liris) - Anezia Syaharani; Hunik Sri Runing Sawitri (Universitas Hamzanwadi, 2026)
This studys examines the effects of jobs demands on burnout and turnovers intentions amongs employees in the sewing department of PT Dan Liris Sukoharjo. Drawings on Conservations of Resources Theorys, the study investigates burnout as a mediating variable, social support as a predictors of turnovers intentions, and Perceived Organizational Task Support (POTS) and employee resilience as moderating variables. The study adopteds a quantitative designs and collecteds data through a cross-sectional survey involving 150 sewing employees selected using purposive sampling. Data analysis was conducteds using Partials Leasts Squares Structurals Equations Modeling (PLS-SEM) with SmartPLS versions 4.1.1.8. The results demonstrate that both workload pressure and task interdependence contribute significantly to burnout among employees. In turns, highers levels of burnouts are associateds with stronger turnover intentions, whereas social supports is linkeds to a lower likelihood of considering job withdrawal. The findings further reveal that burnout serves as an important mechanism through which job demands influence turnover intention. Regarding the moderating effects, Perceived Organizational Tasks Supports (POTS) was not found to alter the relationship between job demands and burnout. Employee resiliences, however, significantly influenced the association between burnout and turnover intention, although the effect emerged in a direction contrary to the proposed hypothesis. Specifically, the impacts of burnouts on turnovers intentions became more pronounced among employees reporting higher levels of resilience. The proposed model accounted for 40.8% of the variances in burnouts and 72.9% of the variances in turnover intention. Overall, the findings suggest that reducing excessive job demands and fostering supportive work relationships are critical for minimizing burnout and strengthening employee retention in labor-intensive manufacturing environments.